Levels of Satisfaction With Nursing Services of The Patients Presenting to Emergency Units - Gül Mersinlioğlu; Havva Öztürk (Sağlık ve Hemşirelik Yönetimi Dergisi, 2015)
INTRODUCTION: OBJECTIVE: This descriptive study was conducted to detect satisfaction levels regarding nursing services of the patients who applied to emergency units. METHODS: The study was carried out with 302 patients who applied to emergency units of one public hospital, two specialty hospitals and one training and research hospital after getting permissions from the general directorate of public hospitals of Trabzon Province. RESULTS: The data were collected with an information form and Satisfaction with Nursing Care Scale and were tested with numbers, percentages, means, standard deviations, t-test, Mann-Withney U test, ANOVA and Kruskall Wallis tests. According to most of the patients in study were 18-25 ages (28.5%), female (55.3%), married (59.3%), university graduates (37.3%) and 49% of them benefited services of emergency units from time to time. The total score of the scale used to determine satisfaction levels related to nursing services of patient was 3.81+-0.69. The patients were mostly satisfied with nurses' respecting their privacy (4.01+-0.82), their providing the treatment (administering the medicines) in time (3.99+-0.80) and easy communication with the nurses when they needed them (3.95+-0.81). However; patients' satisfaction levels regarding items that the nurses introduced themselves (3.54+-1.10) and the emergency units (3.64+-0.994) and they were introduced to other patients in the units when they came emergency units (3.40+-1.18) were a little lower. Educational status and marital status of the patients were effective upon their satisfaction levels. It was identified that satisfaction levels of those patients who were married and graduated from universities were lower the satisfaction levels of other patients (p<0.05). DISCUSSION AND CONCLUSION: CONCLUSION: As a result; patients who accepted to emergency units were generally satisfied with nursing services but satisfaction levels of those patients who were married and graduated from universities were not at the desired level.